If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -7x = 8x + 24 Reorder the terms: 6 + -7x = 24 + 8x Solving 6 + -7x = 24 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6 + -7x + -8x = 24 + 8x + -8x Combine like terms: -7x + -8x = -15x 6 + -15x = 24 + 8x + -8x Combine like terms: 8x + -8x = 0 6 + -15x = 24 + 0 6 + -15x = 24 Add '-6' to each side of the equation. 6 + -6 + -15x = 24 + -6 Combine like terms: 6 + -6 = 0 0 + -15x = 24 + -6 -15x = 24 + -6 Combine like terms: 24 + -6 = 18 -15x = 18 Divide each side by '-15'. x = -1.2 Simplifying x = -1.2
| 4.7+.9+.01= | | -88-8x=8x+24 | | 3x+5=-28-8x | | 144-6x=4x+24 | | -16-6x=4x+24 | | 7x-8=4x-4 | | 10x-4=5(x+4) | | 10x-120=4x-12 | | 256-7x=38x+21 | | 8-8x=44-15x | | -78-9x=8x+24 | | 2x+9=-81-8x | | 145-5x=5x+5 | | -22-4x=10-8x | | 10-3(a+2)=4a-1 | | 2x+36=12x-44 | | 6x+3.1=-6x-5.3 | | 8x-3.7=-6x-12.1 | | 5-z=2z-37 | | 9x+3.9=6x+5.4 | | -4x-2.3=5x-5.9 | | 3x+2.8=-6x-3.5 | | 3x-3.7=2x-4.3 | | 5x-1.2=2x | | 4x+34=6x+14 | | 5x+0.3=2x | | 4y-9=-2y | | 4(x-5)=-24 | | 4(x+4)=8 | | 5(x+9)=40 | | 3(3x-2)=4x+9 | | 5(x-1)=10 |